Solid heat medium
Patent Information
- Application Number
- JP2023140825
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
AI Technical Summary
【0007】 本発明者らは、相転移材料の粉体を固化させた固体熱媒体に圧力を印加して得られる放熱量と、当該固体熱媒体から圧力を解放して得られる吸熱量とを良好に確保すべく、鋭意研究を行った。そして、研究の結果、本発明者らは、固体熱媒体に圧力が印加されたときに相転移材料の粉体の一部に圧力が伝達されていないおそれがあることや、固体熱媒体から圧力が解放されたときに相転移材料の粉体の一部が加圧される前の状態にスムースに戻っていないおそれがあることを見出した。これらの知見を踏まえ、本開示の固体熱媒体には、樹脂製粉体添加される。これにより、相転移材料の粉体同士間の空隙を樹脂製粉体で充填することができるので、固体熱媒体に圧力を印加するときに、相転移材料の粉体の全体を概ね均等に加圧することが可能になり、固体熱媒体からの放熱量を良好に確保することができる。更に、相転移材料の粉体同士間の空隙を樹脂製粉体で充填して減少させておくことで、固体熱媒体から圧力が解放されるときに、相転移材料の粉体の全体を加圧される前の状態にスムースに戻すことが可能になるので、固体熱媒体による吸熱量を良好に確保することができる。また、樹脂製粉体として低い熱伝導率を有するものを採用することで、当該樹脂製粉体を固体熱媒体の断熱材として機能させることができる。これにより、固体熱媒体からの熱が対象物に伝達される前に放出されてしまったり、当該固体熱媒体による吸熱と同時に熱が放出されて対象物の温度を低下させ得なくなったりするのを抑制することが可能になる。
Smart Images

Figure 2025034438000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to solid heat transfer media that undergo a phase transition between high and low temperature phases in response to the application and release of pressure. [Background technology]
[0002] Rubidium-manganese-iron cyanide complex (Rb x Mn[Fe(CN) 6 ] y ) is known (see, for example, Patent Document 1). The rubidium-manganese-iron cyano complex exhibits bistability in two states: a high-temperature phase in which the valences of manganese and iron are Mn(II)-Fe(III), and a low-temperature phase in which the valences of manganese and iron are Mn(III)-Fe(II). When pressure is applied to a heat medium containing such a rubidium-manganese-iron cyano complex, the phase transition temperature from the high-temperature phase to the low-temperature phase and the phase transition temperature from the low-temperature phase to the high-temperature phase increase. That is, when pressure is applied to the heat medium, the phase transition temperature from the high-temperature phase to the low-temperature phase, which is lower than the phase transition temperature from the low-temperature phase to the high-temperature phase, increases, so that the rubidium-manganese-iron cyano complex can be caused to undergo a phase transition from the high-temperature phase to the low-temperature phase and heat can be released from the heat medium without significantly lowering the temperature of the heat medium. In addition, when the pressure applied to the heat medium containing the rubidium-manganese-iron cyano complex is released, the phase transition temperature from the high-temperature phase to the low-temperature phase and the phase transition temperature from the low-temperature phase to the high-temperature phase decrease. Therefore, by releasing the pressure applied to the heat medium, it is possible to cause the rubidium-manganese-iron cyano complex to undergo a phase transition from a low-temperature phase to a high-temperature phase, and to have the heat medium absorb heat, without significantly increasing the temperature of the heat medium. By repeatedly applying and releasing pressure to the heat medium, heat can be transferred from a low-temperature part to a high-temperature part via the heat medium. Furthermore, Patent Document 1 discloses a heat absorption and release system including a solid heat medium obtained by solidifying powder of rubidium-manganese-iron cyano complex, and a pressurizing device for pressurizing the solid heat medium. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2023 / 002698 Summary of the Invention [Problem to be solved by the invention]
[0004] However, even if a solid heat medium containing a phase change material as described in Patent Document 1 is subjected to a phase change by applying pressure and then releasing the pressure, it is difficult to obtain the theoretically expected amount of heat dissipation (amount of temperature increase of the solid heat medium) or amount of heat absorption (amount of temperature decrease of the solid heat medium).
[0005] Therefore, a main objective of the present disclosure is to satisfactorily ensure the amount of heat dissipation obtained by applying pressure to a solid heat medium containing a phase change material, and the amount of heat absorption obtained by releasing pressure from the solid heat medium. [Means for solving the problem]
[0006] The solid heat medium of the present disclosure is a solid heat medium obtained by solidifying powder of a phase-change material that undergoes a phase transition from a high-temperature phase to a low-temperature phase in response to the application of pressure and that undergoes a phase transition from the low-temperature phase to the high-temperature phase in response to the release of pressure, and contains a resin powder as an additive.
[0007] The present inventors have conducted intensive research in order to ensure a good heat release amount obtained by applying pressure to a solid heat medium obtained by solidifying powder of a phase-change material, and a good heat absorption amount obtained by releasing pressure from the solid heat medium. As a result of the research, the present inventors have found that when pressure is applied to the solid heat medium, the pressure may not be transmitted to a part of the powder of the phase-change material, and when pressure is released from the solid heat medium, a part of the powder of the phase-change material may not smoothly return to the state before pressure was applied. Based on these findings, a resin powder is added to the solid heat medium of the present disclosure. This allows the resin powder to fill the gaps between the powder particles of the phase-change material, so that when pressure is applied to the solid heat medium, the entire powder of the phase-change material can be pressurized almost evenly, and the heat release amount from the solid heat medium can be ensured. Furthermore, by filling and reducing the gaps between the powder particles of the phase-change material with the resin powder, when the pressure is released from the solid heat medium, the powder particles of the phase-change material can be smoothly restored to the state before pressure was applied, so that the amount of heat absorbed by the solid heat medium can be secured well. In addition, by using a resin powder having a low thermal conductivity, the resin powder can function as a heat insulating material for the solid heat medium. This makes it possible to prevent the heat from the solid heat medium from being released before being transferred to the object, or to prevent the heat from being released simultaneously with the heat absorption by the solid heat medium, making it impossible to lower the temperature of the object. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a cross-sectional view showing a heat absorption and dissipation system including a solid heat medium according to the present disclosure. [Diagram 2] FIG. 1 is a cross-sectional view showing a heat absorption and dissipation system including a solid heat medium according to the present disclosure. [Diagram 3] 1 is a table showing the evaluation results of the amount of heat released obtained by applying pressure to a solid heat transfer medium of a comparative example not containing an additive. [Figure 4] 1 is a table showing the evaluation results of the amount of heat absorption obtained by releasing pressure from a solid heat transfer medium of a comparative example not containing an additive. [Diagram 5]1 is a table showing the evaluation results of the amount of heat dissipation obtained by applying pressure to the solid heat transfer medium of the present disclosure. [Figure 6] 1 is a chart showing the evaluation results of the amount of heat absorption obtained by releasing pressure from the solid heat transfer medium of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Next, an embodiment of the present disclosure will be described with reference to the drawings.
[0010] FIG. 1 is a schematic diagram showing a heat absorption and dissipation system 1 including a solid heat medium 5 according to the present disclosure. The heat absorption and dissipation system 1 shown in the figure includes a container 2, a receiving member 3, a pressure member 4, and a solid heat medium 5. The container 2 is formed into a cylindrical shape from a heat insulating material. The receiving member 3 is formed into a disk shape, and is fixed inside the lower end of the container 2 to form the bottom of the container 2. The pressure member 4 is supported by the inner peripheral surface of the container 2 so as to be slidable in the axial direction of the container 2, and is moved in the axial direction of the container 2 by a driving device (not shown). The solid heat medium 5 is a rubidium-manganese-iron cyano complex (Rb x Mn[Fe(CN) 6 ] y (hereinafter referred to as "RbMnFe complex"), and is formed into a substantially cylindrical shape having an outer diameter smaller than the inner diameter of the container 2 by solidifying the RbMnFe complex, which is an insoluble powder, with a binder. The solid heat transfer medium 5 is placed inside the container 2 such that its outer circumferential surface does not contact the inner circumferential surface of the container 2, and its lower end surface in the figure contacts the upper surface (bottom surface) of the receiving member 3 in the figure. The pressurizing member 4 is placed inside the container 2 such that its lower surface in the figure contacts the upper end surface in the figure of the solid heat transfer medium 5.
[0011] The RbMnFe complex is a charge-transfer phase transition complex that has a network structure in which iron and manganese are three-dimensionally cross-linked by cyano groups, and has a crystal structure in which rubidium ions are arranged alternately in the voids of the framework. Such RbMnFe complexes exhibit bistability in two states: a high-temperature phase in which the valences of manganese and iron are Mn(II)-Fe(III), and a low-temperature phase in which the valences of manganese and iron are Mn(III)-Fe(II). In other words, the RbMnFe complex has a first phase transition temperature T LH When heated to above the first phase transition temperature T LH The second phase transition temperature T HL Below this temperature, a phase transition occurs from the high-temperature phase to the low-temperature phase, releasing heat.
[0012] In addition, the phase transition of the RbMnFe complex is accompanied by thermal hysteresis, and after the RbMnFe complex undergoes a phase transition from the low-temperature phase to the high-temperature phase, it stores the heat absorbed during the phase transition to the high-temperature phase until it transitions back to the low-temperature phase. Furthermore, by changing the ratio of rubidium to manganese in the RbMnFe complex, the two phase transition temperatures T LH ,T HL and the phase transition temperature T LH and the phase transition temperature T HL In the RbMnFe complex forming the solid heat transfer medium 5, the ratio x of rubidium to manganese is set to 0.94≦x≦1. This changes the phase transition temperature T LH and the phase transition temperature T HL and the phase transition temperature T LH ,T HL The rate of change of magnetic susceptibility (gradient of change) in the vicinity can be made larger.
[0013] Furthermore, when the RbMnFe complex is pressurized, the phase transition temperature from the high-temperature phase to the low-temperature phase, T HL and the phase transition temperature T from the low-temperature phase to the high-temperature phase LH Basically, the higher the pressure applied to the RbMnFe complex, the higher the phase transition temperatures T HL ,T LHTherefore, as shown in FIG. 2, if the pressure member 4 is moved toward the receiving member 3 by a driving device (not shown) to apply pressure to the solid heat transfer medium 5, the phase transition temperature T LH The phase transition temperature T from the high-temperature phase to the low-temperature phase is lower than HL Since the temperature of the solid heat medium 5 becomes high, it is possible to cause the RbMnFe complex to undergo a phase transition from a high-temperature phase to a low-temperature phase without significantly lowering the temperature of the solid heat medium 5. As a result, in the heat absorption and dissipation system 1, by applying pressure to the solid heat medium 5 by the pressurizing member 4, heat is released from the solid heat medium 5 to a heating target (not shown) in response to the phase transition of the RbMnFe complex from the high-temperature phase to the low-temperature phase, and the heating target can be heated. When pressure is applied to the solid heat medium 5, the solid heat medium 5 contracts in the axial direction and expands in the radial direction so that its outer circumferential surface comes into contact with the inner circumferential surface of the container 2, as shown in FIG. 2.
[0014] In contrast, when the pressure applied to the RbMnFe complex is released, the phase transition temperature from the high-temperature phase to the low-temperature phase, T HL and the phase transition temperature T from the low-temperature phase to the high-temperature phase LH decreases (returns to original state). Therefore, by releasing the pressure applied to the solid heat medium 5 (reducing the applied pressure to zero), it becomes possible to cause the RbMnFe complex to undergo a phase transition from a low-temperature phase to a high-temperature phase without significantly increasing the temperature of the solid heat medium 5. As a result, in the heat absorption and dissipation system 1, by releasing the pressure applied to the solid heat medium 5 (see FIG. 1), the solid heat medium 5 can absorb heat from a cooling target (not shown) in response to the phase transition of the RbMnFe complex from the low-temperature phase to the high-temperature phase, thereby cooling the cooling target. When the pressure is released from the solid heat medium 5, the solid heat medium 5 expands in the axial direction and contracts in the radial direction so that the outer circumferential surface is separated from the inner circumferential surface of the container 2.
[0015] In addition, by doping the Fe in the RbMnFe complex with trivalent cobalt ions, more specifically, hexacyanocobalt ions, the phase transition temperature T LHFor example, if the amount of cobalt doped in the RbMnFe complex is 0 to 7%, the phase transition temperature T HL is set to a value in the range of 248K to 307K, and if it is 2 to 7%, the phase transition temperature T HL can be set to a value within the range of 248 K to 290 K. Furthermore, by doping the Mn (manganese) of the RbMnFe complex with divalent copper (Cu) ions, divalent nickel (Ni) ions, or divalent zinc (Zn) ions, the phase transition temperature T LH More specifically, the doping amount of divalent copper (Cu) ions relative to Mn in the RbMnFe complex is set to, for example, 6 to 8%, or the doping amount of divalent nickel (Ni) ions or divalent zinc (Zn) ions is set to, for example, 2 to 8%, thereby lowering the phase transition temperature T HL can be set to a value within a range of 250 K to 290 K. In addition, even if the Mn in the RbMnFe complex is doped with divalent iron (Fe) ions, if the doping amount is kept low (for example, 4% or less), the phase transition temperature T LH can be reduced.
[0016] On the other hand, when the Mn (manganese) of the RbMnFe complex is doped with divalent cobalt (Co) ions, the phase transition temperature T LH This makes it possible to realize a heat absorption / dissipation system that operates in a high-temperature environment by using divalent cobalt ions as a dopant for the RbMnFe complex. In addition, when zinc is used as a dopant for the RbMnFe complex, the phase transition temperature T LH and the phase transition temperature T HL By setting the doping amount to 4-8%, it is possible to reduce the difference (hysteresis width) between the phase transition temperature T LH and the phase transition temperature T HL The difference (hysteresis width) between the phase transition temperature T LHand the phase transition temperature T HL Therefore, an increase in the difference (hysteresis width) between the measured value and the actual value can be effectively suppressed.
[0017] Here, even if a conventional solid heat medium containing the above-mentioned RbMnFe complex undergoes a phase transition by applying pressure or releasing pressure, it is difficult to obtain the theoretically expected heat release amount (temperature rise amount of the solid heat medium) or heat absorption amount (temperature drop amount of the solid heat medium). For this reason, the present inventors have conducted intensive research in order to satisfactorily secure the heat release amount obtained by applying pressure to a solid heat medium obtained by solidifying powder of the RbMnFe complex and the heat absorption amount obtained by releasing pressure from the solid heat medium. In the research, the present inventors evaluated the heat release amount obtained by applying pressure to a comparative solid heat medium that does not contain an additive, and the heat absorption amount obtained by releasing pressure from the comparative solid heat medium that does not contain an additive. The comparative solid heat medium is a RbMnFe complex doped with 9% divalent zinc (Zn) ions relative to Mn (manganese) and solidified into a roughly cylindrical shape by pressurizing it inside a mold without adding any additive.
[0018] FIG. 3 shows the evaluation results of the amount of heat dissipation obtained by applying pressure to a comparative solid heat medium containing no additive. FIG. 3 shows the temperature change at the center (the center of the central cross section in the axial direction) of the solid heat medium when a pressure of 500 MPa is applied to the comparative solid heat medium for a predetermined time (for example, about 30 seconds) by a test device having a configuration similar to that of the heat absorption and dissipation system 1 in an environment where the room temperature is about 20°C. The maximum temperature rise when a pressure of 500 MPa is applied to the comparative solid heat medium was 18°C. Therefore, even if the comparative solid heat medium is applied to the heat absorption and dissipation system 1, it is difficult to heat the heating target well.
[0019] FIG. 4 shows the evaluation results of the amount of heat absorption obtained by applying pressure to a comparative solid heat medium containing no additive and then releasing the pressure from the solid heat medium. FIG. 4 shows the temperature change at the center of the solid heat medium (the center of the central cross section in the axial direction) when a pressure of 500 MPa is applied to the comparative solid heat medium for a predetermined time by the above-mentioned test device in an environment where the room temperature is about 20°C, and then the pressure is released from the solid heat medium. The maximum temperature drop when a pressure of 500 MPa is applied to the comparative solid heat medium and then the pressure is released is 12°C. Therefore, even if the comparative solid heat medium is applied to the heat absorption and release system 1, it is difficult to cool the cooling target well.
[0020] After obtaining the evaluation results of Figures 3 and 4, the inventors further analyzed and considered the cause of the insufficient amount of heat released from and the insufficient amount of heat absorbed by the solid heat medium containing no additives. As a result, the inventors found that when pressure is applied to the solid heat medium, the pressure may not be transmitted to a part of the powder of the RbMnFe complex, and when pressure is released from the solid heat medium, a part of the powder of the RbMnFe complex may not smoothly return to the state before pressure was applied (a part of the solid heat medium may not expand or contract).
[0021] Based on these findings, the present inventors decided to add resin powder to the solid heat medium 5 of the heat absorption and dissipation system 1 formed of the RbMnFe complex. In this embodiment, the resin powder is polypropylene powder with an average particle size of about 5 μm. The solid heat medium 5 is formed into a substantially cylindrical shape by pressing and solidifying a mixture of the powder of the RbMnFe complex doped with 9% divalent zinc (Zn) ions relative to Mn (manganese) and the resin powder inside a mold. The amount of the resin powder added to the solid heat medium 5 is 10% by weight. The resin powder, which is an additive, also functions as a binder for solidifying the powder of the RbMnFe complex.
[0022] FIG. 5 shows the results of an evaluation of the amount of heat dissipation obtained by applying pressure to the solid heat medium 5 to which resin powder has been added. FIG. 5 shows the temperature change at the center of the solid heat medium 5 (the center of the central cross section in the axial direction) when a pressure of 500 MPa is applied to the solid heat medium 5 for a predetermined time (e.g., about 30 seconds) by the above-mentioned testing device in an environment where the room temperature is about 20°C. The maximum temperature rise when a pressure of 500 MPa is applied to the solid heat medium 5 was 29°C. It can be seen from these evaluation results that if the solid heat medium 5 is applied to the heat absorption and dissipation system 1, the object to be heated can be heated satisfactorily.
[0023] FIG. 6 shows the evaluation results of the amount of heat absorption obtained by applying pressure to the solid heat medium 5 to which the resin powder has been added and then releasing the pressure from the solid heat medium 5. FIG. 6 shows the temperature change at the center of the solid heat medium 5 (the center of the cross section at the center in the axial direction) when a pressure of 500 MPa is applied to the solid heat medium 5 for a predetermined time by the above-mentioned test device in an environment where the room temperature is about 20°C, and then the pressure is released from the solid heat medium 5. The maximum temperature drop when a pressure of 500 MPa is applied to the solid heat medium 5 and then the pressure is released is 24°C. From these evaluation results, it can be understood that if the solid heat medium 5 is applied to the heat absorption and dissipation system 1, the cooling target can be cooled well.
[0024] That is, in the solid heat transfer medium 5 to which the resin powder is added, the gaps between the powder particles of the RbMnFe complex can be filled with the resin powder. As a result, when pressure is applied to the solid heat transfer medium 5, the entire powder particles of the RbMnFe complex can be pressurized almost uniformly, and the amount of heat released from the solid heat transfer medium 5 can be secured well. Furthermore, by filling and reducing the gaps between the powder particles of the RbMnFe complex with the resin powder, when pressure is released from the solid heat transfer medium 5, the entire powder particles of the RbMnFe complex can be smoothly restored to the state before pressure was applied, and the amount of heat absorbed by the solid heat transfer medium 5 can be secured well. In addition, by adopting a resin powder having a low thermal conductivity such as polypropylene powder, the resin powder can function as a heat insulating material for the solid heat transfer medium 5. As a result, it is possible to suppress the heat from the solid heat transfer medium 5 from being released before being transferred to the heating target, or the heat being released simultaneously with the heat absorption by the solid heat transfer medium 5, making it impossible to lower the temperature of the cooling target.
[0025] Furthermore, by adding polypropylene powder to the solid heat medium 5, it is possible to effectively reduce the gaps between the powder particles of the RbMnFe complex and further improve the heat insulating property of the solid heat medium 5. However, the solid heat medium 5 may be one to which a resin powder (e.g., polytetrafluoroethylene powder) that can be broken down to a particle size similar to that of the RbMnFe complex has been added, instead of the polypropylene powder.
[0026] Considering the characteristics of polypropylene powder and polytetrafluoroethylene powder, the resin powder added to the solid heat transfer medium 5 is preferably one having a compressive yield stress of 55 MPa or less. This makes it possible to fill the gaps between the RbMnFe complex powder particles when the RbMnFe complex powder is solidified, and to stably retain the resin powder in the gaps. However, the resin powder may be any material having a compressive yield stress of 55 MPa or more as long as it is deformed by the pressure applied to cause the RbMnFe complex to undergo a phase transition.
[0027] Furthermore, in consideration of the characteristics of polypropylene powder and polytetrafluoroethylene powder, the resin powder added to the solid heat transfer medium 5 should have a particle size of 20 μm or less, more preferably 5 μm or less. This makes it possible for the resin powder mixed into the RbMnFe complex powder or the resin powder crushed by pressure to satisfactorily fill the gaps between the RbMnFe complex powder particles. However, the resin powder may have a fine particle size comparable to the particle size of the RbMnFe complex, and is not necessarily limited to a particle size of 5 μm or 20 μm or less.
[0028] In addition, in consideration of the characteristics of polypropylene powder and polytetrafluoroethylene powder, it is preferable that the resin powder added to the solid heat transfer medium 5 has a thermal conductivity of 0.25 W / m·K or less. This makes it possible to further improve the heat insulation of the solid heat transfer medium 5. However, the resin powder may have a relatively low thermal conductivity, and is not necessarily limited to one having a thermal conductivity of 0.25 W / m·K or less.
[0029] Furthermore, the solid heat transfer medium 5 contains a RbMnFe complex as a phase transition material. This allows the phase transition temperature T LH The phase transition temperature T from the high-temperature phase to the low-temperature phase is lower than HL Since the pressure applied to the solid heat medium 5 becomes high, the RbMnFe complex can undergo phase transition from a high-temperature phase to a low-temperature phase, and heat can be released from the solid heat medium 5, without significantly lowering the temperature of the solid heat medium 5. In addition, by releasing the pressure applied to the solid heat medium 5, the RbMnFe complex can undergo phase transition from a low-temperature phase to a high-temperature phase, and heat can be absorbed by the solid heat medium 5, without significantly increasing the temperature of the solid heat medium 5.
[0030] However, the phase transition material forming the solid heat transfer medium 5 is not limited to the RbMnFe complex, and may be TiNi, BaTiO 3 , PbZr 0.95 Ti 0.05 O 3The solid heat medium 5 may be an alloy containing Ti (elastic heat medium) such as Ti-containing alloy (elastic heat medium), or an organic resin containing hydrogen bonds (pressure heat medium) such as neopentyl glycol (NPG), pentaerythritol (PE), or pentaglycerin (PE). 5 S 2 Ge 2 , La(Fe,Co,Si) 13 , MnCoGeB 0.02 , PVDF-TrFE, Cu 2 It may be an elastocaloric material such as ZnAl or FeRh, and (NH 4 )SO 4 , AgI, rubber, AMP, TRIS, MNP, and NMP.
[0031] The present disclosure is not limited to the above embodiment, and various modifications can be made within the scope of the present disclosure. Furthermore, the above embodiment is merely a specific form of the invention described in the Summary of the Invention, and does not limit the elements of the invention described in the Summary of the Invention. [Industrial Applicability]
[0032] The present disclosure is applicable to the solid heat transfer medium manufacturing industry and the like. [Explanation of symbols]
[0033] 1 heat absorption and dissipation system, 4 pressure member, 5,5' solid heat medium.
Claims
1. A solid heat transfer medium obtained by solidifying a powder of a phase-transition material that undergoes a phase transition from a high-temperature phase to a low-temperature phase in response to application of pressure and that undergoes a phase transition from the low-temperature phase to the high-temperature phase in response to release of pressure, A solid heat transfer medium containing resin powder as an additive.
2. The solid heat transfer medium according to claim 1, The resin powder is a solid heat transfer medium having a particle size that allows the voids between the powder particles to be filled when the powder of the phase change material is solidified.
3. 3. The solid heat transfer medium according to claim 1, wherein the resin powder has a compressive yield stress of 55 MPa or less.
4. 3. The solid heat transfer medium according to claim 1, wherein the resin powder has a thermal conductivity of 0.25 W / m·K or less.
Citation Information
Patent Citations
Heat absorption / release system
WO2023002698A1